2016
DOI: 10.3109/00365521.2015.1102318
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum levels of high sensitive C-reactive protein and inflammation activity in chronic gastritis patients

Abstract: Although serum hs-CRP is not a specific biomarker for gastritis, elevated hs-CRP levels may be considered as a predictive marker of changes in gastric mucosa and a promising therapeutic target for patients with gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…We determined in our study population with chronic gastritis that the mean of hs-CRP was 1.9±1.6 mg/dl for males and 2.2±1.9 mg/dl for females, which was higher 1 mg/dl than the normal hs-CRP level 9 . Consistent with to the studies in literature, it is found increased hs-CRP levels in parallel to the severity of HP gastritis compared to gastritis without HP infection in our study 6 , 12 . In adition, we also found that serum hs-CRP level of chronic gastritis patients with HP infection was significantly higher than those without HP infection and there was significant association between severity of HP infection and hs-CRP level.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We determined in our study population with chronic gastritis that the mean of hs-CRP was 1.9±1.6 mg/dl for males and 2.2±1.9 mg/dl for females, which was higher 1 mg/dl than the normal hs-CRP level 9 . Consistent with to the studies in literature, it is found increased hs-CRP levels in parallel to the severity of HP gastritis compared to gastritis without HP infection in our study 6 , 12 . In adition, we also found that serum hs-CRP level of chronic gastritis patients with HP infection was significantly higher than those without HP infection and there was significant association between severity of HP infection and hs-CRP level.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to being an indicator of inflammation, hs-CRP has been suggested to be a marker of cardiovascular diseases and gastric cancer in patients with HP-associated chronic gastritis 6 , 11 . Although serum level of hs-CRP has been known to increase in chronic gastritis with HP infection, limited studies have focused on the association of hs-CRP level with inflammatory activity and presence of precancerous lesions in biopsy specimens 11 , 12 . If hs-CRP level is predictive of inflammation level and precancerous lesions, it can be used as a simple and easily accesible laboratory test in early diagnosis, treatment response monitoring, and cancer screening in chronic gastritis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Infiltration of lymphocytes and plasma cells in the lamina propria were considered as signs of chronic gastritis and neutrophil infiltration was considered as sign of active gastritis. The presence of goblet cells and replacement of mucosal cylindrical cells by absorption cells was considered as a sign of intestinal metaplasia (17) .…”
Section: Histologymentioning
confidence: 99%
“…Atherosclerosis as a chronic inflammatory disease is a multifactorial inflammatory phenomenon and it is known that some pathogens is associated with chronic infection can induce inflammation (12) . In the case of H. pylori infection, the organism after colonization, by activating proinflammatory signaling pathways such as nuclear factor kappa B (NF-κB) (8) , can cause the production and release of the proinflammatory cytokines such Flow mediated dilation and carotid intima media thickness in patients with chronic gastritis associated with Helicobacter pylori infection as CRP, mRNA and protein expression of tumor necrosis factor alpha (TNFα) and interleukin (17) . Systemic effect of this inflammatory process is a basic hypothesis of the association between H. pylori infection and extragastrointestinal (GI) diseases (15) .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic gastritis is a chronic inflammation of the gastric mucosa, which is characterized by the infiltration of inflammatory cells and has a high incidence in China [1,2]. The active period of CG is an important precancerous period of gastric cancer, which is one of the most frequently occurring cancers in the world, but the pathogenesis of CG is not clear [3,4].…”
Section: Introductionmentioning
confidence: 99%